PENGARUH DEBT TO ASSET RATIO DAN KEPEMILIKAN INSTITUSIONAL PADA KEBIJAKAN DIVIDEN DENGAN FREE CASH FLOW SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Saidah, Alvi; Rambe, Rizki Fillhayati; Arief, Muhammad (Mount Hope Management International Journal, 2025)
This study aims to determine the effect of Debt to Asset Ratio and Institutional Ownership on Dividend Payout Ratio moderated by Free Cash Flow in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The research method used is the associative method with a quantitative approach. The research sample consisted of 180 financial reports obtained from 36 companies. The results of the study indicate that Debt to Asset Ratio (DAR) has a negative and significant effect on Dividend Payout Ratio (DPR), Institutional Ownership (KI) does not affect Dividend Payout Ratio (DPR), Free Cash Flow (FEF) cannot moderate the effect of Debt to Asset Ratio (DAR) on Dividend Payout Ratio (DPR), and Free Cash Flow (FEF) cannot moderate the effect of Institutional Ownership on Dividend Payout Ratio (DPR) in Manufacturing companies listed on the IDX in 2018-2022.